Characterisation of nanoparticle emissions and exposure at traffic intersections through fast–response mobile and sequential measurements. (April 2015) - Goel, Anju; Kumar, Prashant
Abstract: Quantification of disproportionate contribution made by signalised traffic intersections (TIs) to overall daily commuting exposure is important but barely known. We carried out mobile measurements in a car for size–resolved particle number concentrations (PNCs) in the 5–560 nm range under five different ventilation settings on a 6 km long busy round route with 10 TIs. These ventilation settings were windows fully open and both outdoor air intake from fan and heating off (Set1 ), windows closed, fan 25% on and heating 50% on (Set2 ), windows closed, fan 100% on and heating off (Set3 ), windows closed, fan off and heating 100% on (Set4 ), and windows closed, fan and heating off (Set5 ). Measurements were taken sequentially inside and outside the car cabin at 10 Hz sampling rate using a solenoid switching system in conjunction with a fast response differential mobility spectrometer (DMS50). The objectives were to: (i) identify traffic conditions under which TIs becomes hot–spots of PNCs, (ii) assess the effect of ventilation settings in free–flow and delay conditions (waiting time at a TI when traffic signal is red) on in–cabin PNCs with respect to on–road PNCs at TIs, (iii) deriving the relationship between the PNCs and change in driving speed during delay time at the TIs, and (iv) quantify the contribution of exposure at TIs with respect to overall commuting exposure. Congested TIs were found to become hot–spots when vehicle accelerate from idling conditions. In–cabin peak PNCs followed similar temporal trend as for on–road peak PNCs. Reduction in in–cabin PNC with respect to outside PNC was highest (70%) during free–flow traffic conditions when both fan drawing outdoor air into the cabin and heating was switched off. Such a reduction in in–cabin PNCs at TIs was highest (88%) with respect to outside PNC during delay conditions when fan was drawing outside air at 25% on and heating was 50% on settings. PNCs and change in driving speed showed an exponential–fit relationship during the delay events at TIs. Short–term exposure for ∼2% of total commuting time in car corresponded to ∼25% of total respiratory doses. This study highlights a need for more studies covering diverse traffic and geographical conditions in urban environments so that the disparate contribution of exposure at TIs can be quantified. Graphical abstract: Highlights: Particle number size distributions were measured inside and outside the car. Peak number concentration at traffic signal was 29-fold of those during free–flow. Size-resolved inside to outside concentration ratio follows a power-law fit form. Number concentration is exponentially dependent on driving speed at intersections. About 2% of total commuting time at intersections corresponded to ∼25% of total doses.